2016
DOI: 10.1021/acs.iecr.6b00506
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study of Reactions of Aniline and Benzoyl Chloride Using NH3 as Acid Absorbent in a Microstructured Chemical System

Abstract: NH 3 was used as acid absorbent to intensify the reactions between aniline and benzoyl chloride in a microstructured chemical system in this work. By suppressing the side reaction, the addition of NH 3 could reduce the reaction time needed for 99% reactants conversation to less than 1/10 of the condition without NH 3 . Furthermore, a complete kinetic model containing two rapid main reactions and two reversible consecutive side reactions was established, and six reaction rate constants and their corresponding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
(49 reference statements)
1
7
0
Order By: Relevance
“…Using this with K = 0.0024 ± 2 × 10 –4 (Figure S10), and an oil-phase MPD diffusivity D o = 1630 ± 90 μm 2 /s (Figure S11), in eq reveals a reaction rate constant k = 110 ± 35 L/mol·s. This compares well with the rate constant measured for the analogous reaction between aniline and benzoyl chloride (monofunctional versions of monomers used here) in N -methyl-2-pyrrolidone, for which k = 128–164 L/mol·s. , Given that N -methyl-2-pyrrolidone is a more polar solvent which stabilizes the charged transition state, the slightly smaller value reported here for k seems reasonable …”
supporting
confidence: 84%
See 1 more Smart Citation
“…Using this with K = 0.0024 ± 2 × 10 –4 (Figure S10), and an oil-phase MPD diffusivity D o = 1630 ± 90 μm 2 /s (Figure S11), in eq reveals a reaction rate constant k = 110 ± 35 L/mol·s. This compares well with the rate constant measured for the analogous reaction between aniline and benzoyl chloride (monofunctional versions of monomers used here) in N -methyl-2-pyrrolidone, for which k = 128–164 L/mol·s. , Given that N -methyl-2-pyrrolidone is a more polar solvent which stabilizes the charged transition state, the slightly smaller value reported here for k seems reasonable …”
supporting
confidence: 84%
“…This compares well with the rate constant measured for the analogous reaction between aniline and benzoyl chloride (monofunctional versions of monomers used here) in N-methyl-2-pyrrolidone, for which k = 128−164 L/ mol•s. 35,36 Given that N-methyl-2-pyrrolidone is a more polar solvent which stabilizes the charged transition state, the slightly smaller value reported here for k seems reasonable. 37 The previous discussion holds for the early stage in the reaction, where transport resistance due to a dense film is absent.…”
mentioning
confidence: 67%
“…H 2 SO 4 and hydrocarbon feed were delivered into the membrane dispersion microreactor (with the average diameter of 5 μm) by metering pumps (Beijing Satellite Co., Ltd.), respectively. The details of the reactor have been presented in our previous work . The delay loop (an inner diameter of 2 mm and an external diameter of 3 mm) with different length was connected to the reactor.…”
Section: Methodsmentioning
confidence: 99%
“…Microstructured chemical systems show obvious advantages in kinetics measurement because of their good dispersion and the precise control of reaction time, as well as reaction conditions, especially for the rapid reaction of a heterogeneous system. Plenty of kinetics studies were conducted in microstructured chemical systems, especially for a fast reaction controlled by mass transfer. Zhang et al obtained the reaction kinetics of dehydrochlorination of dichloropropanol in a microstructured chemical system, showing distinct values for reaction mechanism understanding . Wang et al conducted experiments on the kinetics study of an aniline and benzoyl chloride reaction in a microstructured chemical system .…”
Section: Introductionmentioning
confidence: 99%
“…A kinetic study of reactions of aniline and benzoyl chloride using ammonia as acid absorbent in a micro structured chemical system was conducted by Wang et al [3]. They found that the reaction time is reduced by 99 % when ammonia was used compared to condition without ammonia.…”
Section: Introductionmentioning
confidence: 99%